Growth and serum mineral profile of broiler starter fed dried cocoyam tuber (colocasia esculenta) meal - M. U., Onyekwere; P. C., Jiwuba; S. O., Okechukwu; A. C., Anuonye (International Journal of Biological Research, 2016)
A 30-day experiment was conducted with 240 unsexed broiler starters to determine the effect of cocoyam tuber meal on growth and serum mineral profile. Four diets were formulated at 0%, 10%, 20% and 30% of cocoyam tuber meal. The birds were assigned the four treatment diets in a completely randomized design and replicated 3 times with 20 birds per replicate. Feed and water were supplied ad-libitum. Data were collected on average daily feed intake, average daily weight gain, feed conversion ratio and blood was sampled from each treatment group, data obtained were analysed statistically. The performance of the broiler starter birds showed significant (p
Keywords: Broilers; Performance; Serum; Mineral Profile and Cocoyam Tuber Meal.